Differences between the MODIS Collection 6 and 5.1 aerosol datasets over the greater Mediterranean region. (December 2016) - Georgoulias, A.K.; Alexandri, G.; Kourtidis, K.A.; Lelieveld, J.; Zanis, P.; Amiridis, V.
Abstract: The most recent release of MODIS atmospheric product (Collection 6) is already used in studies concerning the greater Mediterranean region. However, an assessment of the differences and similarities of the last two MODIS collections (6 and 5.1) is missing. In this paper, a first comparison of the MODIS/Terra and Aqua Collection 6 and Collection 5.1 AOD at a wavelength of 550 nm (AOD550 ) data is presented with a focus on the Mediterranean region. It is shown that Collection 6 AODs are either higher or lower than Collection 5.1 AODs over different continental areas while, over ocean, Collection 6 AODs are higher almost everywhere (11% for MODIS/Terra and 8% for MODIS/Aqua). Generally, Collection 6 retrieves higher AODs than Collection 5.1, especially for MODIS/Terra. The evaluation of Collection 6 and 5.1 AOD550 data against sunphotometric observations from 23 AERONET stations in the area reveals that Collection 6 exhibits a better agreement with the ground-based data. The Collection 6 AOD550 data exhibit a statistically significant negative trend of the order of about −0.001/year (∼−0.5%/year) for MODIS/Terra and −0.002/year (∼−1.0%/year) for MODIS/Aqua. For the region studied, Collection 6 trends are largely reduced compared to Collection 5.1 trends by ∼0.003/year for MODIS/Terra data while for MODIS/Aqua data the trends have not changed significantly (only by ∼0.0003/year). Highlights: Assessment of the differences of the last two MODIS Collections (6 and 5.1). Col. 6 AODs are either higher or lower than Collection 5.1 AODs over land. Col. 6 AODs are higher than Collection 5.1 AODs almost everywhere over ocean. Col. 6 AODs exhibit a statistically significant negative trend. Col. 6 trends are reduced compared to Col. 5.1 trends for MODIS Terra.